A new species of the Miniopterus schreibersii species complex (Chiroptera: Miniopteridae) from the Maghreb Region, North Africa - Puechmaille, Sebastien J.; Allegrini, Benjamin; Benda, Petr; Gürün, Kanat; Šrámek, Jan; Ibañez, Carlos; Juste, Javier; Bilgin, Rasit (Zootaxa, 2014)
We used an integrative approach combining cranio-dental characters, mitochondrial and nuclear data and acoustic data to show the presence in the genus Miniopterus of a cryptic species from the Maghreb region. This species was previously recognised as Miniopterus schreibersii (Kuhl, 1817). Miniopterus maghrebensis sp. nov. can be differentiated from M. schreibersii sensu stricto on the basis of cranial characters and from mitochondrial DNA and microsatellite evidence. Although slight external morphological and acoustic differences were noted between the two species, these criteria alone did not allow reliable species identification from live animals. Based on the specimens identified morphologically and/or genetically, the distribution range of M. maghrebensis sp. nov. extends from northern Morocco to south of the High Atlas Mountains and northern Tunisia. The new cryptic species is found in sympatry with M. schreibersii s.str. near coastal regions of North Africa.